Bacterial Spectrum and Associated Sociodemographic Factors in Pediatric Blood Stream Infections at Tertiary Care Hospital - Hafsa Maria Ishrat, Shaista Ehsan, Nazish Fatima, Tayyaba Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the bacterial spectrum and the frequency of sepsis in infants and children presenting to a tertiary care hospital, as well as its association with sociodemographic factors. Methods: This retrospective cross-sectional research was performed at the Department of Pediatrics, Ziauddin University Hospital Karachi. A total of 199 children records in the age group from 29 days to 12 years of age with a report of positive blood culture were included in the study. Non-probability consecutive sampling technique was used. Records were reviewed retrospectively and demographic data collected such as gender, age, diagnosis, type of admission (medical or surgical), length of stay in the hospital, and primary diagnosis with associated co-morbidities. SPSS was used for statistical analysis. The findings of quantitative variables were reported in terms of mean and standard deviation and qualitative variables in terms of frequency and percentages. Inferential statistics were analyzed by using Chi-square for comparing positivity of culture with baseline characteristics and a p-value of ≤0.05 was considered significant. Results: The mean age of the study population and the mean duration of hospital stay were 45.95±37.15 months and 7.61±3.61 days respectively. Out of a total of 199 cases with positive blood culture findings for bacterial isolates, coagulase negative staphylococci were found in 95(47.7%), Staphylococci Aureus in 57(28.6%), Streptococci species in 54(27.1%), E. Coli in 24(12.1%), Pseudomonas Aeruginosa in 14(7%), Klebsiella Pneumonia in 13(6.5%), Enterococcus species in 11(5.5%). Practical implication: Sepsis in the pediatric age group is associated with a high mortality and increased length of hospital stay. Early diagnosis and prompt treatment is the key to improve outcome of sepsis. Conclusion: There is a high prevalence of sepsis in children less than 48 months of age, more commonly in children with incomplete vaccination, female gender, decreased maternal educational level and a lower socioeconomic status especially in blood culture positive cases with unusual organisms such as Pseudomonas, Acinetobacter and gram-negative bacilli Keywords: Sepsis, Tertiary care, Pediatric intensive care, gram positive organism